MITRAGYNA SPECIOSA-INDUCED HEPATOTOXICITY-TREATED EFFECTIVELY BY PIPER BETLE: SCOPE AS A FUTURE ANTIDOTE - Haslan, Haszianaliza; Haji Suhaimi, Farihah; Das, Srijit (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Â Objective: Consumption of Mitragyna speciosa (MS) leads to various toxicities including hepatotoxicity. Piper betle (PB) is a herb that possesses various therapeutic properties. The aim of the present study was to examine the protective effect of PB methanol extract (PBME) on MS-induced hepatotoxicity which could pave the way for any future antidote. Methods: Twenty-four male Spragueâ€“Dawley rats were randomized into control and experimental groups. The control group was further divided into the negative (G-T80) and positive (G-PB) control groups. The G-T80 group (n=6) received oral gavage of the vehicle, 15% Tween 80. The G-PB group (n=6) received PBME 200 mg/kg/day, orally. The experimental group was divided into two groups, i.e., The G-MS and G-MS (PB) groups. The G-MS group (n=6) received only MS methanol extract (MSME) 500 mg/kg/day, while the G-MS (PB) group (n=6) received MSME with concomitant treatment with PBME. Results: Histopathology examination of the G-T80 and G-PB groups showed normal histology of the liver. The G-MS group showed liver injury features such as microvesicular steatosis, ballooning degeneration, acidophilic bodies, scattered focal necrosis, fibrous portal expansion, bridging fibrosis, sinusoidal congestion, and dilatation. These features were fewer in the G-MS (PB) group which received concomitant treatment with PBME. Conclusion: Administration of PBME exerted a protective effect against MS-induced hepatotoxicity. Future clinical trials using PB as an antidote may help in combating MS-induced hepatoxicity.